2008
DOI: 10.1099/jmm.0.2008/003814-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mycoplasma pneumoniae in adult community-acquired pneumonia by PCR and serology

Abstract: Diagnosis of pneumonia caused by Mycoplasma pneumoniae in adults is hampered by a lack of rapid and standardized tests for detection. This prospective study was conducted to compare the diagnostic values of an indirect immunofluorescence assay and a 16S rRNA gene PCR for the diagnosis of M. pneumoniae pneumonia in adults. From February 2005 to January 2008, 357 patients (53.8 % males, median age 63 years, range 18-94) admitted for community-acquired pneumonia (CAP) to two hospitals in Santiago, Chile, were enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 28 publications
(42 reference statements)
1
38
3
Order By: Relevance
“…In the present study, the infection rate of M. pneumoniae detected by serology was 46.6% among hospitalized CAP patients. This rate was significantly higher than those (6.8%-29.6%) previously detected by various methods in most studies [12][13][14][15][16]. However, this rate is consistent with the one recently reported by Tao et al in Chinese patients with CAP, in whom M. pneumoniae infection was the most frequently identified pathogen, detected by serological tests in 38.9% of CAP patients and in 45.7% and 24.4% of young (< 65 years of age) and old patients, respectively [10].…”
Section: Discussioncontrasting
confidence: 64%
“…In the present study, the infection rate of M. pneumoniae detected by serology was 46.6% among hospitalized CAP patients. This rate was significantly higher than those (6.8%-29.6%) previously detected by various methods in most studies [12][13][14][15][16]. However, this rate is consistent with the one recently reported by Tao et al in Chinese patients with CAP, in whom M. pneumoniae infection was the most frequently identified pathogen, detected by serological tests in 38.9% of CAP patients and in 45.7% and 24.4% of young (< 65 years of age) and old patients, respectively [10].…”
Section: Discussioncontrasting
confidence: 64%
“…However, because about 60% of patients in the All-B group were suspected to have developed aspiration pneumonia, treatment to cover anaerobic pathogens should be prescribed for patients with decreased ADL. Second, previous studies indicated that the sensitivity of IgM antibodies against Mycoplasma pneumoniae was 33.3% (26). Therefore, our diagnosis using IgM against Mycoplasma pneumoniae might be insufficient.…”
Section: Discussionmentioning
confidence: 89%
“…In accordance with the current study data, Morozumi (26) and Medjo (22) found similar specificities, while the sensitivity rates were higher in their studies than those of the current study. On the other hand, some researchers reported lower sensitivity and specificity of PCR method in comparison with those of the IgG serology (24,27). These differences in the results of such studies could be due to PCR types (conventional PCR or RT-PCR), gene targets used for amplification reaction, sample type, or time of sampling.…”
Section: Discussionmentioning
confidence: 79%
“…There are some controversies about the gold standard method to diagnose M. pneumoniae. Some authors indicated that the bacterial culture is a gold standard (23), while others mentioned that PCR or serology tests were the gold standard methods to diagnose acute Mycoplasma infection (24). In the current study, the acute infection was diagnosed in 16 cases, based on the combination of an IgM (25).…”
Section: Discussionmentioning
confidence: 94%